HIPEC ROC I: A phase i study of cisplatin administered as hyperthermic intraoperative intraperitoneal chemoperfusion followed by postoperative intravenous platinum‐based chemotherapy in patients with platinum‐sensitive recurrent epithelial ovarian cancer. Issue 3 (17th June 2014) - Zivanovic, Oliver; Abramian, Alina; Kullmann, Maximilian; Fuhrmann, Christine; Coch, Christoph; Hoeller, Tobias; Ruehs, Hauke; Keyver‐Paik, Mignon Denise; Rudlowski, Christian; Weber, Stefan; Kiefer, Nicholas; Poelcher, Martin L.; et al.
<x xml:space="preserve">Abstract</x> This phase I study tested the safety, feasibility, pharmacokinetics and pharmacodynamics of cisplatin administered as hyperthermic intraoperative intraperitoneal chemoperfusion (HIPEC) in patients with platinum‐sensitive recurrent epithelial ovarian cancer (EOC) undergoing secondary cytoreductive surgery followed by postoperative platinum‐based intravenous chemotherapy. Twelve patients with operable, recurrent platinum‐sensitive EOC (recurrence ≥6 months after first‐line therapy) were included according to the classical 3+3 dose‐escalation design at three dose levels—60, 80 and 100 mg/m2. After surgical cytoreduction, a single dose of cisplatin was administered via HIPEC for 90 min at 41–43°C. Postoperatively, all patients were treated with standard intravenous platinum‐based combination chemotherapy. One of six patients experienced a dose‐limiting toxicity (grade 3 renal toxicity) at a dose of 100 mg/m2. The remaining five patients treated with 100 mg/m2 tolerated their treatment well. The recommended phase II dose was established at 100 mg/m2. The mean peritoneal‐to‐plasma AUC ratio was 19·5 at the highest dose level. Cisplatin‐induced DNA adducts were confirmed in tumor samples. Common postoperative grade 1–3 toxicities included fatigue, postoperative pain, nausea, and surgical site infection. The ability to administer standard intravenous platinum‐based chemotherapy after HIPEC was uncompromised. Cisplatin administered as HIPEC at a dose of 100 mg/m2 has an acceptable safety profile in selected patients undergoing secondary cytoreductive surgery for platinum‐sensitive recurrent EOC. Favorable pharmacokinetic and pharmacodynamic properties of HIPEC with cisplatin were confirmed at all dose levels, especially at 100 mg/m2. The results are encouraging to determine the efficacy of HIPEC as a complementary treatment in patients with EOC.